3(-2+x)=6+3x

Simple and best practice solution for 3(-2+x)=6+3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(-2+x)=6+3x equation:


Simplifying
3(-2 + x) = 6 + 3x
(-2 * 3 + x * 3) = 6 + 3x
(-6 + 3x) = 6 + 3x

Add '-3x' to each side of the equation.
-6 + 3x + -3x = 6 + 3x + -3x

Combine like terms: 3x + -3x = 0
-6 + 0 = 6 + 3x + -3x
-6 = 6 + 3x + -3x

Combine like terms: 3x + -3x = 0
-6 = 6 + 0
-6 = 6

Solving
-6 = 6

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| -18+6=-4(x+6) | | 20t-15=18x-7 | | 6x-2=2(2x+6) | | 2222+m=35 | | 9x-4=5(2x-3) | | 3x+4x=-x+7m | | -1.2y+.8=-.76 | | 7x+1=2(2x+2) | | 44+m=35 | | h(t)=-16t^2+122t+10 | | 6x-1=4(x-1) | | 4+m=35 | | .5x+.07=.25x+.57 | | -7/13p=-4 | | x^4-4x^3-30x^2-8x-64=0 | | 4x-2=102 | | -6n+-2=16 | | 5r(8r-5)(5r-1)=0 | | 3+8X= | | 19x-5=11x-21 | | 4x+10=3(2x+5) | | 5(12w+1)= | | 16-3.4d=-8 | | 9+3=612 | | 7x+2=3(3x+1) | | 8n-12=40 | | (7+x)/2+3=12 | | 155*22/31*18/25 | | 5a-12=88 | | 9/8*4/5 | | 12-(4m+4)=3+3m-16 | | 2(x-5)+1=-(x+3) |

Equations solver categories